Analisis Perbandingan Produktivitas Tukang dan Pekerja Menggunakan Metode Time Study dan Analisis Harga Satuan Pekerjaan 2022 - Alnisa, Putri; Nuswantoro, Waluyo; Waluyo, Rudi (Jurnal Talenta Sipil, 2024)
The working time of handymen and workers before project implementation can be calculated from the labor coefficient in units of work quantity so that productivity can be known. However, between productivity based on the 2022 AHSP coefficient and field productivity often experience differences. This study aims to calculate the productivity of handymen and workers using the time study method and the comparison of the productivity of handymen and workers the time study method against the 2022 AHSP labor coefficient in the construction of projects in Palangka Raya City for red brick wall installation work. Data collection techniques with observation by recording work time and quantity of work as well as the number of handymen and workers. The data was analyzed using the time study method assisted by Microsoft Excel. The results showed that worker productivity: 6.38 m2⁄OH and handyman: 5.83 m2⁄OH. Comparison of work productivity using the time study method to the productivity of the 2022 AHSP coefficient in red brick wall installation work shows that worker productivity has a greater value and builders have a smaller value than productivity based on the 2022 AHSP coefficient.